2012
DOI: 10.1370/afm.1363
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Multimorbidity and Morbidity Burden for Use in Primary Care and Community Settings: A Systematic Review and Guide

Abstract: PURPOSE Many patients consulting in primary care have multiple conditions (multimorbidity). Aims of this review were to identify measures of multimorbidity and morbidity burden suitable for use in research in primary care and community populations, and to investigate their validity in relation to anticipated associations with patient characteristics, process measures, and health outcomes.METHODS Studies were identifi ed using searches in MEDLINE and EMBASE from inception to December 2009 and bibliographies.RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
479
1
33

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(522 citation statements)
references
References 61 publications
(68 reference statements)
9
479
1
33
Order By: Relevance
“…Other studies found the same results 9,17 . This finding can be explained by studies that show that elderly people with multimorbidity have a poorer quality of life, a deficit in self-care of health, and a greater degree of dependence in daily life, with negative repercussions on functional capacity 22 . As the number of diseases increases, physical, social and mental complications occur in the elderly, resulting in a worsening of self-perception of health 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies found the same results 9,17 . This finding can be explained by studies that show that elderly people with multimorbidity have a poorer quality of life, a deficit in self-care of health, and a greater degree of dependence in daily life, with negative repercussions on functional capacity 22 . As the number of diseases increases, physical, social and mental complications occur in the elderly, resulting in a worsening of self-perception of health 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This uncontrolled consumption may also cause clinical alterations, or even drug interactions which have adverse effects on the elderly 22,25 . Understanding how morbidities interact with one another has a greater clinical relevance than simply counting the number of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found an association between diseases 44 and negative self-rated health 3,17 (the more the diseases, the higher the prevalence of negative self-rated health). Elderly with three or more diseases present worse quality of life 45,46 , worse health conditions 45 , and more difficulty in performing ADL and consequently worse functional capacity 45 . These elements may lead older individuals with 3 or more diseases to rate their health less optimistically.…”
Section: Discussionmentioning
confidence: 99%
“…10 With both self-report data and medical claims coding, the CCI has been shown to be associated with service use, costs, and mortality in primary care. 11,12 Depression. Trained research assistants used the Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV), to diagnose major depressive disorder (MDD).…”
Section: Key Variables Under Studymentioning
confidence: 99%